Millennials' Deals with Plastic: The Effect of Natural Environmental Orientation, Environmental Knowledge, and Environmental Concern on Willingness to Reduce Plastic Waste - Nihayatu Aslamatis Solekah; Tanti Handriana; Indrianawati Usman (Journal of Consumer Sciences, 2022)
To maintain environmental sustainability can be managed and resolved by changing human behavior, especially by reducing plastic waste. This study investigated whether natural environmental orientation, environmental knowledge, environmental concern, and environmental attitude affect the extent to which millennials avoid or reduce the purchase of single-use plastic tableware, food with plastic packaging, and plastic water bottles called Willingness to Reduce Plastic Waste (WRPW). This study used quantitative using the purposive sampling method. Data collection techniques using online questionnaires were sent to respondents with criteria for educated millennial Muslims at Islamic universities in East Java, Central Java, and West Java. The survey was conducted for three months and obtained 369 respondents. The questionnaire is processed by using SEM analysis with Smart PLS. The results show that environmental knowledge provides a direct and an indirect effect on willingness to reduce plastic waste through environmental attitude. Meanwhile, environmental concern has no direct effect on willingness to reduce plastic waste, yet it has an indirect effect through environmental attitude. This research implies that concern for the environment is not necessarily accompanied by the willingness to reduce the use of plastic. However, adequate knowledge about the environment can increase the willingness to reduce the use of plastic among millennial generations who prioritize logical thinking and adapt to their knowledge.